2007
DOI: 10.1677/joe-06-0101
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effects of chorionic gonadotropin hormone on human adipose development

Abstract: It is well known that pregnancy is associated with fat weight gain. However, the mechanisms whereby fat mass accumulation is controlled during this period are poorly understood. Therefore, we attempted to determine whether human chorionic gonadotropin (HCG), in vitro, influences human adipose tissue development and/or metabolism. For the first time, HCG/LH receptor was characterized in human adipose cells. We also demonstrated that physiological concentrations of HCG, while unaltering both lipolysis and expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 81 publications
1
29
0
Order By: Relevance
“…Thus, Lappas et al (2005) reported that in human adipose tissue and placental tissues explants, exogenous leptin increased the secretion of tumour necrosis factor (TNF)-α, interleukin (IL)-1β and IL-6, as had already been reported for human chorionic gonadotropin (hCG) in cytotrophoblasts (Chardonnens et al, 1999). Recent data has brought this regulatory pathway full circle by indicating that hCG exerts a proadi pogenic e ect in human preadipocytes by simulating leptin secretion (Dos Santos et al, 2007). Most signi cantly, the regulation of proin ammatory cytokines produced in the intrauterine environment, may suggest roles for leptin in regulating endometrial attachment (Schulz et al, 2009), modulating myometrial contractility, cervical ripening, and the rupture of conceptus membranes (Lappas et al, 2005), all of which signi cantly impact the processes associated with parturition.…”
Section: Mechanisms Of Cadmium-related Placental Effectsmentioning
confidence: 65%
“…Thus, Lappas et al (2005) reported that in human adipose tissue and placental tissues explants, exogenous leptin increased the secretion of tumour necrosis factor (TNF)-α, interleukin (IL)-1β and IL-6, as had already been reported for human chorionic gonadotropin (hCG) in cytotrophoblasts (Chardonnens et al, 1999). Recent data has brought this regulatory pathway full circle by indicating that hCG exerts a proadi pogenic e ect in human preadipocytes by simulating leptin secretion (Dos Santos et al, 2007). Most signi cantly, the regulation of proin ammatory cytokines produced in the intrauterine environment, may suggest roles for leptin in regulating endometrial attachment (Schulz et al, 2009), modulating myometrial contractility, cervical ripening, and the rupture of conceptus membranes (Lappas et al, 2005), all of which signi cantly impact the processes associated with parturition.…”
Section: Mechanisms Of Cadmium-related Placental Effectsmentioning
confidence: 65%
“…In a previous study, the CG/LHR was detected in human adipose tissue (Dos Santos et al 2007). In our study, we first analysed the expression of the CG/LHR in insulinsensitive cells (3T3-L1 adipocytes and C2C12 myoblasts) by RT-PCR.…”
Section: Cg/lh Receptors Are Expressed At Low Levels In Insulin-sensimentioning
confidence: 83%
“…CG has also been characterised as a novel angiogenic factor in human endothelial cells (Zygmunt et al 2002). Dos Santos et al (2007) reported that CG/LHR is expressed in human primary adipocytes and that the proadipogenic effect of CG in human preadipocytes leads to the increased fat storage that occurs during the first trimester of pregnancy. In this study, we first confirmed that mature 3T3-L1 adipocytes and C2C12 CG activates the IKKB/NF-kB signalling pathway in 3T3-L1 adipocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous data have demonstrated the involvement of both C/EBP and Sp1 transcription factors in the regulation of leptin gene in adipocytes (Mason et al 1998). Moreover, the C/EBP transcription factor expression was reported to be regulated by hCG in the follicular development (Sirois & Richards 1993), in rat primary cultures of Leydig cells and in human adipose cells (Nalbant et al 1998, Dos Santos et al 2007.…”
Section: Leptin Promoter Organization and Transcription Factors Involmentioning
confidence: 97%